Relationships among parenting knowledge, quality of stimulation in the home and child academic performance - Baharudin, Rozumah (Universiti Putra Malaysia Press, 1999)
The present study determined the relationships among parenting knowledge, quality of stimulation in the home, and children's academic performance. Subjects were 60 Malay mothers with children aged 8 to 9 years, who were identified using stratified random selection. Data were collected by interview and observation in the home of the respondents. Parenting knowledge was measured using an instrument that was specially developed by the researcher. The quality of stimulation in the home was assessed using Caldwell and Bradley's (1984) HOME inventory. Information on the children's academic achievement was obtained from their school report cards. Results show significant associations among the variables of interest. Parenting knowledge was significantly related to the quality of stimulation in the home, which in turn, was significantly related to the academic performance of the children. Additional analyses show significant associations between family background factors (education, family income, and number of children) and parenting knowledge, and quality of stimulation in the home environment. Implications of the findings are discussed.